Gut Microbiota as a Prospective Therapeutic Target for Curcumin: A Review of Mutual Influence - Wissam Zam (Journal of Nutrition and Metabolism)
Background. Turmeric is a spice that has recently received much interest and has been widely used in Ayurvedic medicine. Turmeric products are diarylheptanoids and have been characterized as safe. They are termed as curcuminoids that consists essentially of three major compounds: curcumin, demethoxycurcumin, and bisdemethoxycurcumin. Curcumin is a lipophilic polyphenol that has poor systemic bioavailability and suffers from biotransformation by human intestinal microflora to yield different metabolites that are easily conjugated to glucuronides and sulfate O-conjugated derivatives. Recently, an increasing number of studies have indicated that dysbiosis is linked with many metabolic diseases, though gut microbiota could be a novel potential therapeutic target. Scope and Approach. Thus, it is suspected that curcumin and its derivatives exert direct regulative effects on the gut microbiota which could explain the paradox between curcumin’s poor systemic bioavailability and its widely reported pharmacological activities. Key Findings and Conclusions. This article summarizes a range of studies that highlight the interaction between curcumin and gut microbiota and considers opportunities for microbiome-targeting therapies using turmeric extract.